Pelaksanaan Metode Pembelajaran Akidah Akhlak Pada Masa New Normal Di Taman Pendidikan Al-Qur’an (TPA) Arsyad Kelurahan Nankodok Kota Payakumbuh - Raihan Muhammad Iqbal; Iswantir (Program Studi Akuntansi IKOPIN, 2022)
Thesis with the title Implementation of Akidah Akhlak Learning Methods in the New Normal Period at Arsyad Al-Qur'an Education Park (TPA) in Nankodok Village, Payakumbuh City, written by Raihan Muhammad Iqbal (NIM. 217029), Islamic Religious Education Study Program (PAI) , Faculty of Tarbiyah and Teacher Training (FTIK), State Islamic Institute (IAIN) Bukittinggi in 2021. The background for writing this thesis is that during the New Normal period, the Akidah Akhlak learning method applied by the TPA teacher was not optimal, for example during the Akidah Akhlak learning process the TPA teacher used a learning method that bored students, so that it had an impact on students' understanding of the lack of Akidah learning. Morals. This TPA teacher is lacking in the practice of learning Akidah Akhlak, the teacher only explains material that is limited to theory without any practice. This TPA teacher is also less varied in combining several learning methods that will be delivered to students, teachers tend to use only one learning method in the learning process. The approach used in this study is a qualitative approach, meaning that researchers will see phenomena that occur in society. In this study, researchers used a form of qualitative descriptive research. The key informants in this study were TPA teachers, while supporting informants were TPA administrators and TPA students in Nankodok Village. The research technique for collecting data used in this thesis is interviews and observation and is also supported by documentation. The collected data was then analyzed using qualitative analysis techniques. After conducting the research, the results were found: (1) the implementation of the lecture method when learning morals, the teacher had carried out the lecture method steps, some of which were in accordance with the theory. The implementation of this lecture method has the advantage that it makes it easier for teachers to explain and control students during learning. (2) The obstacles faced by teachers during Akidah Akhlak learning are the use of masks that make students and teachers alike have difficulty hearing each other's voices, then the teacher also difficulties in controlling the class during learning. Learning by TPA teachers only uses voice in explaining learning, this causes students to get bored and do other things during learning. This is a drawback of implementing the lecture method. The teacher's effort in overcoming this is the teacher reprimanding the students and returning the students' focus on learning. There are still some students who do not understand the learning of Akidah Akhlak when asked questions are held. To overcome this, the teacher instructs students to study hard at home about what is learned at the TPA.